Analisis Kepuasan dan Loyalias Konsumen Roti Unyil Venus di Bogor - Mekaniwati, Ani (Jurnal Ilmiah Manajemen Kesatuan, 2017)
The objectives of this research is to analyze the model of relationship between customerâ€™s level of satisfaction and their loyalty to â€œroti unyilâ€ and to construct the strategic implication to improve this satisfaction and loyalty.The research was conducted in June 2017. The data were collected from 100 respondents and were analyzed using structural equation modeling (SEM) analysis and two-top boxes to measure customer satisfaction index. The results showed that contribution of customerâ€™s satisfaction on customerâ€™s loyalty was 0.49 and the most significant dimensions for customerâ€™s satisfaction were human resources (0.40), promotion (0.15), and place (0.08). Most attributes had high customer satisfaction index, with parking access (56%) and viral marketing (59%) were the lowest ones